L’ora della gioventù. Gerarchie di valori e distinzione intergenerazionale tra uomini kanak che rubavano auto - Miceli, Martino (Antropologia Pubblica, 2024)
In Kanaky/New Caledonia, car theft, generally carried out against the descendants of European settlers, is a widespread phenomenon among Kanak youth cohorts. The so-called ‘Generation 1984’, from the year the nationalist claim exploded in many of its members were born, however, seems to be the one most deeply connected by my interlocutors with the genesis of this practice. Despite the fact that car theft is much earlier, this generation has for a time taken on specific traits that have made its relationship to car theft a key element in its definition. Today, however, many of its members tend to employ rhetorical strategies of delegitimising the theft practices of younger people, claiming a different hierarchy of values. In this article, we want to show how the reassertion of the ‘practical’ and ‘moral’ rupture claimed by older people with respect to the actions of younger people actually fits in as a mechanism for the reproduction of a social order based on age-related qualities and is an instrument for the regeneration of Kanak society in the east of the country’s main island.